Depreciation in the Canadian Airline Industry. (September 2014) - Bujaki, Merridee; Durocher, Sylvain
Abstract This case is designed to help students enhance their analytical skills and link accounting policy choices with corporate strategy. Written initially for MBA students and senior analysts attending executive education sessions, it provides participants with 1) industry background for the Canadian airline sector, and 2) historical and selected financial and non‐financial information from the annual reports and initial public offering documents of three players in this industry. Participants are invited to reflect on the theoretical and practical reasons underlying the choice of a depreciation method by airline companies, to find ways to quantitatively compare companies that use different depreciation methods, and to link these policy choices to possible strategic considerations. This case is based on a unique situation prevailing in 2009 where financial information was available for all three airlines which were using different approaches for aircraft depreciation.